Induction of Mycobacterium Tuberculosis Lipid-Specific T Cell Responses by Pulmonary Delivery of Mycolic Acid-Loaded Polymeric Micellar Nanocarriers - Shang, Shaobin; Kats, Dina; Cao, Liang; Morgun, Eva; Velluto, Diana; He, Ying; Xu, Qichen; Wang, Chyung-Ru; Scott, Evan A. (Frontiers in Immunology, 2018)
Mycolic acid (MA), a major lipid component of the Mycobacterium tuberculosis (Mtb) cell wall, can be presented by the nonpolymorphic antigen presenting molecule CD1b to T cells isolated from Mtb-infected individuals. These MA-specific CD1b-restricted T cells are cytotoxic, produce Th1 cytokines and form memory populations, suggesting that MA can be explored as a potential subunit vaccine candidate for TB. However, the controlled elicitation of MA-specific T cell responses has been challenging due to difficulties in the targeted delivery of lipid antigens and a lack of suitable animal models. In this study, we generated MA-loaded micellar nanocarriers (MA-Mc) comprised of self-assembled poly(ethylene glycol)-bl-poly(propylene sulfide) (PEG-PPS) copolymers to enhance intracellular delivery of MA to phagocytic immune cells. Using humanized CD1 transgenic (hCD1Tg) mice, we found these nanobiomaterials to be endocytosed by bone marrow-derived dendritic cells (DCs) and localized to lysosomal compartments. Additionally, MA-Mc demonstrated superior efficacy over free MA in activating MA-specific TCR transgenic (DN1) T cells in vitro. Following intranasal immunization, MA-Mc were primarily taken up by alveolar macrophages and DCs in the lung and induced activation and proliferation of adoptively transferred DN1 T cells. Furthermore, intranasal immunization with MA-Mc induced MA-specific T cell responses in the lungs of hCD1Tg mice. Collectively, our data demonstrates that pulmonary delivery of MA via PEG-PPS micelles to DCs can elicit potent CD1b-restricted T cell responses both in vitro and in vivo, and MA-Mc could be explored as a component of subunit vaccines against Mtb infection.